(untitled) (Homoeopathy for All, 2024)
Now a days the most commonly seen conditions during postnatal care are postpartum blues or baby blues and postpartum depression. Postpartum Blues or Baby Blues are acute in nature and happen to as many as 70% of women in the days right after childbirth. Women experience sudden mood swings such as crying for no reason or feeling very impatient, restless, anxious, lonely or sad. Baby blues may last for a few hours or as long as 1 to 2 weeks post delivery. Usually they don’t need any medical intervention from a health care provider. But , joining a support group of new moms or talking with other moms often helps.